A cost-effective novel biochemical fertilizer for better managing nutrient levels and vegetative growth in the immature oil palm (Elaeis guineensis Jacq.) - Peng, Shih Hao Tony; Chee, Kheng Hoy; Mohd Saud, Halimi; Yusop, Mohd Rafii; Tan, Geok Hun (Multidisciplinary Digital Publishing Institute, 2022)
The oil palm (OP) Elaeis guineensis is a robust feeder of nutrients and necessitates the adjustment and adequate allocation of nutrients for optimum growth and yields. Therefore, information on leaf nutrient concentrations during the immature stage is essential for maximal OP yield at the mature stage. Currently, in Malaysia, fertilizer by the standard practice application (Treatment 1; T1) is considered a cost-effective fertilization practice in terms of fertilization cost and the overall cost per palm oil tree per hectare. However, there is an idea to further reduce the costs of fertilizers and labour per hectare to make it more cost-effective. Therefore, the present study aims to develop a novel biochemical fertilizer by testing the Universiti Putra Malaysia (UPM) biochemical fertilizer (Treatment 2; T2) in the immature OP. Since the use of T1 has been well established in Malaysia, the present study is to compare the leaflets’ nutrient levels (nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), and boron (B)) and vegetative parameters (frond length (FL), frond number of leaves (FNL), frond width (FW), frond thickness (FT), chlorophyll index (CI), and the canopy of immature OP by using T2 to compare with those in T1. This study was conducted 6 to 48 months after planting (MAP) at the Telang OP plantation, Kuala Lipis (Pahang), from January 2015 to December 2018. Based on the chemical levels of the pre-treatment soil samples collected at the weeded circle area in January 2015 in the two depths (0–15 cm and 15–30 cm), there was no significant difference (p > 0.05) in all 11 chemical parameters (pH, total N, organic carbon (Org C), total P, available P (Av P), cation exchange capacity (CEC), exchangeable K, (Ex K), exchangeable Ca (Ex Ca), exchangeable Mg (Ex Mg), exchangeable aluminium (Ex Al) and B between T1 and T2. This indicated that the chemical levels in the OP soils in both T1 and T2 would not be significant factors when T1 and T2 were applied. All six leaflets’ nutrient levels showed at least ‘Optimum’ or ‘Excessive’ compared to the established guideline using T1 and T2. Overall, there was no significant (p > 0.05) difference in all the above six leaflets’ nutrient levels and six vegetative parameters between T1 and T2 based on the t-Test, multiple linear stepwise regression analysis, and correlation analysis. These results suggested that rates of T1 and T2 applied in this study are enough to provide the amount of nutrients needed to support the OP vegetative growth during the immature period. The estimated cost savings for the combination of T2 fertilizers per hectare (RM 1113.43 or 250 USD) and reduction of the number of rounds (RM 133.85; or 30 USD) of T2 fertilizer application would give a sum of total cost savings of at least RM 1247.25 (280 USD) per hectare. If only based on the T2 fertilizer per hectare, the economic benefit of the total cost saving is estimated to be at least 10.6%. In summary, this study recommends the utilization of T2 as a novel, cost-effective, and alternative biochemical fertilizer treatment for better management of immature OP plantations in Malaysia.